2013
DOI: 10.3109/13693786.2012.692489
|View full text |Cite
|
Sign up to set email alerts
|

Minimum inhibitory concentrations of amphotericin B, azoles and caspofungin againstCandidaspecies are reduced by farnesol

Abstract: The objective of this study was to evaluate the antifungal activity of farnesol and its interaction with traditional antifungals against drug-resistant strains of Candida species. To do so, we studied the minimum in vitro inhibitory concentration (MIC) of amphotericin B (AMB), fluconazole (FLC), itraconazole (ITC), caspofungin (CAS) and farnesol against 45 isolates of Candida spp., i.e., 24 C. albicans, 16 C. parapsilosis and 5 C. tropicalis through the use of the broth microdilution method. Then, the isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 26 publications
6
55
1
2
Order By: Relevance
“…More recently, many studies have described the activity of farnesol against different species of fungi (15)(16)(17)(18). In this study, for the first time, the antifungal activity of farnesol against the primary pathogen C. posadasii, the causative agent of coccidioidomycosis, was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, many studies have described the activity of farnesol against different species of fungi (15)(16)(17)(18). In this study, for the first time, the antifungal activity of farnesol against the primary pathogen C. posadasii, the causative agent of coccidioidomycosis, was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Derengowski et al demonstrated the in vitro activity of farnesol against the dimorphic fungus Paracoccidioides brasiliensis, which presented an average MIC of 25 M (16). Moreover, recent studies from our group performed with the species Cryptococcus neoformans and C. gattii showed MIC values ranging from 0.29 to 75 M for both species (17), while the farnesol MICs ranged from 9.37 to 150 M against different Candida species (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, farnesol is a quorum-sensing molecule of Candida albicans, controlling factors such as density, cell morphogenesis (Hornby et al, 2001) and biofilm formation (Ramage et al, 2002). Currently, its potential antifungal effects have been reported against different fungal pathogens Cordeiro et al, 2013). In this context, the present study evaluated the in vitro inhibitory effect of farnesol against the dimorphic fungus H. capsulatum var.…”
Section: Discussionmentioning
confidence: 99%
“…Brilhante et al showed that farnesol had an inhibiting activity alone and in combination with antifungal agents against strains of dimorphic fungi from the genus Coccidioides and against Candida spp. clinical isolates [4,5]. Nerolidol shows a toxic effect against, inter alia, Salmonella enterica, Staphylococcus aureus, Escherichia coli and Aspergillus niger, and increases the antibacterial activity of antibiotics [6,7].…”
Section: Figurementioning
confidence: 99%
“…Structures of geranyl acetone (1); nerolidol (2); farnesal (3); farnesol (4) and farnesyl acetate (5).…”
Section: Figurementioning
confidence: 99%